PREVALENCE AND RISK FACTORS OF MICROVASCULAR COMPLICATIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS ATTENDING A TERTIARY CARE CENTRE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Microvascular complications such as diabetic retinopathy, nephropathy, and neuropathy are major causes of morbidity in patients with type 2 diabetes mellitus (T2DM). Their early detection and identification of associated risk factors are crucial for preventing progression. Objectives: To determine the prevalence and risk factors of microvascular complications among patients with T2DM attending a tertiary care center. Methods: A cross-sectional observational study was conducted among 300 patients with T2DM attending a tertiary care hospital. Clinical, biochemical, and anthropometric parameters were recorded. Screening for diabetic retinopathy, nephropathy, and neuropathy was performed using standard methods. Associations between complications and risk factors were analyzed using logistic regression. Results: The overall prevalence of any microvascular complication was 38.3%. Diabetic neuropathy (24.7%) was the most common, followed by nephropathy (21.3%) and retinopathy (18.0%). Increasing age (>50 years), duration of diabetes (>10 years), poor glycemic control (HbA1c ≥8%), hypertension, dyslipidemia, and obesity were independently associated with microvascular complications (p